Pharmacological Properties, Therapeutic Potential and Molecular Mechanisms of JWH133, a CB2 Receptor-Selective Agonist - Hashiesh, Hebaallah Mamdouh; Sharma, Charu; Goyal, Sameer N.; Jha, Niraj Kumar; Ojha, Shreesh (Frontiers in Pharmacology, 2021)
The endocannabinoid system has attracted attention as a pharmacological target for several pathological conditions. Cannabinoid (CB2)-selective agonists have been the focus of pharmacological studies because modulation of the CB2 receptor (CB2R) can be useful in the treatment of pain, inflammation, arthritis, addiction, and cancer among other possible therapeutic applications while circumventing CNS-related adverse effects. Increasing number of evidences from different independent preclinical studies have suggested new perspectives on the involvement of CB2R signaling in inflammation, infection and immunity, thus play important role in cancer, cardiovascular, renal, hepatic and metabolic diseases. JWH133 is a synthetic agonist with high CB2R selectivity and showed to exert CB2R mediated antioxidant, anti-inflammatory, anticancer, cardioprotective, hepatoprotective, gastroprotective, nephroprotective, and immunomodulatory activities. Cumulative evidences suggest that JWH133 protects against hepatic injury, renal injury, cardiotoxicity, fibrosis, rheumatoid arthritis, and cancer as well as against oxidative damage and inflammation, inhibits fibrosis and apoptosis, and acts as an immunosuppressant. This review provides a comprehensive overview of the polypharmacological properties and therapeutic potential of JWH133. This review also presents molecular mechanism and signaling pathways of JWH133 under various pathological conditions except neurological diseases. Based on the available data, this review proposes the possibilities of developing JWH133 as a promising therapeutic agent; however, further safety and toxicity studies in preclinical studies and clinical trials in humans are warranted.